Ethnosemiotics: A Literature Review - Prihatin, Yulianah; Haris Supratno; Mintowati; Anas Ahmadi (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2023)
Ethnosemiotics studies how meaning is interpreted within a culture. The purpose of this study is to characterise the use of ethnosemiotic theories and identify their problematic elements. A review of the literature is part of this research process. This study examines five publications that address ethnoemiotics. Reputable publications, national journals, international seminar proceedings, and dissertation research have all published the five chosen articles. The findings demonstrate that ethnosemiotics is not only regarded as a single, cohesive theory but also that some people employ it as a methodology. In addition, a number of studies view ethnosemiotics as a theory that emerges from the fusion of semiotic theory with other theories including ethnolinguistics, ethnography, and ethnology.